Elements and strategies for ethical decision-making in nursing - Nora, Carlise Rigon Dalla (2016)
This study aimed to identify the elements and strategies that facilitate the ethical decision-making of nurses faced with ethical problems, from publications on the theme. An integrative literature review was carried out. Data collection was performed between the months of April and May 2014, in the databases: SciELO, CINAHL, LILACS and MEDLINE. Original, theoretical and case study articles, with a health team that included nurses, published in Portuguese, English and Spanish were included. A total of 19 studies were selected, the analysis of which resulted in three categories: external factors of ethical decision-making in nursing, individual factors of ethical decision-making in nursing and facilitating strategies of ethical decision-making in nursing. It was concluded that nurses need to use strategies that develop sensitivity, ability and ethical competence, in order to make prudent ethical decisions, contributing to the quality of health care.